Pemberdayaan Dan Pengembangan Entrepreneur-X Melalui Digitalisasi di Medokan Semampir RW 03 Surabaya - Ratnaningsih Sri Yustini; Dyah Rini Prihastuty (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Implementing Community Service (PKM) activities is very important because it will provide an introduction and knowledge about entrepreneurship. Empowerment and development of local potential through digitalization has become the main focus in Medokan Semampir RW 03. This research aims to explain the method of activities carried out in solving problems related to the development of MSMEs in the region. Through this activity method, it is hoped that empowerment and development of local potential can be achieved by improving the problems faced by MSME actors. Steps such as consultation with local authorities, direct approaches to MSME players, as well as providing education and assistance in the form of banners and stickers are expected to help improve marketing and branding of their products. Apart from that, by creating new business ideas such as making grass jelly iced milk, it is hoped that it can encourage innovation and creativity in local businesses. In the process, follow-up and monitoring of MSME actors as well as evaluation of work program results are carried out to ensure the success of implementing solutions and evaluating their effectiveness. It is hoped that the results of this research will provide benefits in improving the economy and strengthening local potential in Medokan Semampir RW 03. By utilizing digitalization and community empowerment holistically, it is hoped that it can create a conducive environment for the development of MSMEs and improve the quality of life of local communities.